The Effect of Trace Ions on the Performance of Reverse Electrodialysis Using Brine/Seawater as Working Pairs - Wang, Zhihao; Li, Jianbo; Wang, Hao; Li, Mengqi; Wang, Lingjie; Kong, Xiangqiang (Frontiers in Energy Research, 2022)
Harvesting the salinity gradient power (SGP) between concentrated brine discharged from seawater desalination installations and seawater and converting into electric energy by reverse electrodialysis (RED) is a promising technique. However, trace ions in brine and seawater may affect the performance of the RED stack, and little attention has been focused on this issue. Therefore, the influences of trace ions in seawater and concentrated brine are analyzed in this work. The effects of these ions on power density, open-circuit voltage, and internal resistance of the RED stack are analyzed by configuring manual seawater and concentrated brine including K1+, Mg2+, SO42-, and Ca2+. Experimental results show that divalent ions (Mg2+, SO42-, and Ca2+) can significantly increase the internal resistance of the RED stack and reduce power density. Mg2+ especially has the largest reduction in the output power of the stack. Oppositely, potassium ions (K1+) in feed solutions will reduce the internal resistance and improve power output. In addition, increasing the salinity gradient of feed solutions, temperature, and flow rate can increase open-circuit voltage and power density, and reduce inner power consumption of the RED stack. This study can provide references for the recovery of SGP in seawater desalination plants.